(untitled) (PJDOL, 2023)
In this study the effects of using interactive whiteboards on the achievement of higher secondary students in respect of English vocabulary teaching were examined. The sample of the study comprised of 80 2nd year students of GCHSS No 1 Haripur District. The study involved two groupsas the experimental group and control group.